STUDI ANALISIS PENGGUNAAN INSTRUMEN PENILAIAN MODEL COMPUTER BASED TEST PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Ismail, Ari Budi; Al Rasyid, Machmud; Muchtarom, Moh (PKn Progresif, 2017)
The purpose of this research are: (1) To know how far Computer Based Test able to accommodate the assessment; (2) To know the lacks and obstacles in the implementation of Computer Based Test.This research used a qualitative research approach. This type of research is descriptive qualitative research. Sources of data obtained from informants, places, events and documents. Sampling technique used is purposive sampling. Data collection techniques used to obtain and compile research data is by interview, observation and document analysis. To obtain the validity of the data used data triangulation and triangulation methods. Data analysis technique using an interactive model consists of data collection, data reduction, data presentation, and conclusion. The research procedure with the following steps: (1) Preparation, (2) Data Collection, (3) Data Analysis, (4) Preparation of Research Reports.Based on the research results, it can be concluded that (1) Computer Based Test is able to accommodate 4 principles of assessment that is Fair, Objective, Educative and Accountable starting from the earliest stages, namely: (a) the rational and systematic planning process assessment of learners in accordance with the valuation principles applicable ; (b) the preparation of an assessment instrument software into the Computer Based Test consider indicators that have been established in accordance with the operational verb mapping grid in question; (c) Implementation of Computer Based Test as an educative assessment activity and conducted for the interests and progress of learners in learning; (d) result of Computer Based Test presented directly; (2) Lack of Computer Based Test is (a) only able to measure cognitive; (B) effectively accommodate the dimensions factual knowledge and conceptual knowledge but weak in procedural knowledge and metacognition knowledge. Barriers experienced in implementing the evaluation of student learning outcomes using the Computer Based Test divided into two technical constraints, the constraints arising out that related to the tools used; and non-technical constraints, the constraints arising from the personnel of learners in the form of readiness and experience of learners in working on the computer-based test.